ANTIBIOTIC SUSCEPTIBILITY PROFILING OF BACTERIA ISOLATED FROM EZE STREAM IN NKPOLOGWU AGUATA FOUND IN ANAMBRA STATE OF NIGERIA, WEST AFRICA. - EZENDIANEFO,; NGOZI (BSc, MEd, MSc), JOSEPHINE (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
This research investigated the antibiotic susceptibility profile of bacteria isolated from Eze stream in Nkpologwu Aguata found in Anambra state of Nigeria. Water experiment was carried out on four (4) samples gotten from diverse points in the Eze stream which were aseptically collected. The samples were analyzed for physicochemical features, Most Probable Number (MPN), biochemical traits and antibiotic susceptibility tests using standard microbiological instrumentation. The results were analyzed through inferential statistics. The bacterial isolates were characterized based on their Gram stain, microscopy, motility and biochemical properties. The degree of susceptibility of the isolates against conventional antibiotics was determined using antibiotics’ impregnated discs.